Золушка: [сказки] / Шарль Перро - Перро Шарль (Детское учебное чтение, 2000)
Экземпляры: ф.11 (20230927) / Инвентарный номер: 63923 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: П 27 / ГРНТИ: 17.82.93 / ББК: 84(4Фра)-45